2020
DOI: 10.1016/j.redox.2020.101758
|View full text |Cite
|
Sign up to set email alerts
|

Protein thiol oxidation in the rat lung following e-cigarette exposure

Abstract: E-cigarette (e-cig) aerosols are complex mixtures of various chemicals including humectants (propylene glycol (PG) and vegetable glycerin (VG)), nicotine, and various flavoring additives. Emerging research is beginning to challenge the “relatively safe” perception of e-cigarettes. Recent studies suggest e-cig aerosols provoke oxidative stress; however, details of the underlying molecular mechanisms remain unclear. Here we used a redox proteomics assay of thiol total oxidation to identify signatures of site-spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 43 publications
4
12
0
Order By: Relevance
“…We did not see significant differences between our bias flow controls and vaping groups, with or without nicotine, which is consistent with a published report of acute vaping in a rat model (Fig. 1C) (7).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We did not see significant differences between our bias flow controls and vaping groups, with or without nicotine, which is consistent with a published report of acute vaping in a rat model (Fig. 1C) (7).…”
Section: Discussionsupporting
confidence: 93%
“…1A). These levels are similar in magnitude to those reported for newborn mice exposed to 1.8% nicotine with PG for ten days and rats exposed to PG/VG + 2.5% nicotine for three days (7, 12). We evaluated histologic changes with acute vaping in the nose and lung.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…First, frozen lung lobes were minced into small pieces on a glass slide placed in an aluminum tray that was chilled by dry ice to prevent the samples from thawing. The minced tissue of each sample was collected into their own 5 mL round bottom polystyrene tube (Corning) and incubated on ice for 30 min in the dark with homogenization buffer (250 mM MES; 1% SDS; 1% Triton X-100) adjusted to pH 6 to protect against artificial oxidation during homogenization, as was used in a previous study of lung tissue [ 42 ]. The pooled total thiol sample was prepared by collecting several pieces of tissue from each minced sample into a single tube.…”
Section: Methodsmentioning
confidence: 99%
“…One lab found WS-23 to be a major component within the nicotine-containing e-liquid-pods, a type of ENDS, given to them by recovered EVALI patients in New York State (Lu, Li et al 2021). Additionally, one study (Jabba, Erythropel et al 2022) found that WS-23 was present in e-cigarettes marketed in the US at levels that may potentially result in exceeding the Margin of Exposure (MOE), a risk Studies so far have shown that exposure to e-cigarette aerosols induces oxidative stress in the lungs (Wang, Zhang et al 2020). Regarding ROS-related e-cigarette studies, studies have shown that total acellular ROS levels in e-cigarette aerosols are dependent on brand, flavor, operational voltage, and puffing protocol, but no studies so far have sought to investigate the role synthetic coolants have in modifying total acellular ROS levels in e-cigarette aerosols (Zhao, Zhang et al 2018).…”
Section: )mentioning
confidence: 99%